Time-sensitive network traffic scheduling method with joint routing planning - Jinchuan PEI; Yuxiang HU; Le TIAN; Tao HU; Ziyong LI (Tongxin xuebao)
To solve the problem of uncertain end-to-end transmission delay caused by the separation of time-sensitive traffic scheduling and routing in time-sensitive network, a multi-constrained traffic scheduling method with joint routing planning was proposed.The inter-flow conflict degree of time-sensitive traffic was introduced to flexibly allocated traffic routing.On that basis, a scheduling constraint model of time-aware shaping and joint conflict-free routing was established to strictly guarantee the time-sensitive traffic scheduling with bounded low latency in both spatial and temporal dimensions.Experimental results show that the proposed method has good delay performance in different topological scenarios, and effectively reduces the delay caused by congestion conflicts under different time-sensitive traffic scales while ensuring link load balancing.